Impact of Inflation Rate, Remittance Income, and Public Loan on Government Expenditure: Evidence Derived from the Nepalese Economy - Dahal, Arjun Kumar; Dhakal, Ghanshyam (Sahayaatra सहयात्रा, 2024)
This study examines the impact of inflation rate, remittance income, and public borrowing on the government's annual expenditure. This study is based on the descriptive and exploratory research design. It follows the positivist research philosophy and quantitative characteristics. It uses secondary data collected from various economic surveys in Nepal and reports from the World Bank. It covers 33 data points from 1990 to 2022. Simple statistical and econometric tools like descriptive statistics, robust regression analysis, Normality test, and confidence interval test are used in this study. The inflation rate, public borrowing, and remittance income are responsible for increasing Nepal's government expenditure. The inflation rate is not individually significant in determining the spending in Nepal. Remittance income has a considerable positive impact on total expenditure in Nepal. One unit increase in remittance income results in a 0.109648 unit increase in government expenditure in Nepal. Likewise, public borrowing is highly significant in explaining government expenditure. One unit increase in public borrowing results in a 1.145037 unit increase in government expenditure in Nepal. Nearly 73.69 percent variation in total government expenditure depends on Nepal's inflation rate, remittance income, and public borrowing. Policymakers in Nepal should focus on bolstering remittance inflows and implementing prudent public borrowing management strategies to foster sustainable economic growth while recognizing the limited influence of the inflation rate on government expenditure.